2017
DOI: 10.1186/s13048-017-0320-9
|View full text |Cite
|
Sign up to set email alerts
|

Serum and peritoneal fluid concentrations of soluble human leukocyte antigen, tumor necrosis factor alpha and interleukin 10 in patients with selected ovarian pathologies

Abstract: BackgroundAlthough immune system plays a key role in the pathogenesis of both endometriosis and ovarian cancer, its function is different. Therefore, we hypothesized, that selected immune parameters can serve as diagnostic markers of these two conditions. The aim of this study was to compare serum and peritoneal fluid concentrations of sHLA-G, IL-10 and TNF-alpha in women with selected ovarian pathologies: benign serous cysts, endometrioma and malignant tumors. Clinical significance of using them for diagnosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…20 In a study evaluating patients with benign ovarian cysts, endometriomas, and ovarian malignancies, serum IL-10 levels were significantly higher in ovarian cancer patients than the other study groups. 21 In the study by Măluţan et al, 23 the serum IL-10 level was also significantly higher in women diagnosed with endometriosis compared to the control group. Evaluating the serum levels of IL-10, our study found a cut-off value of 12.56 pg/mL in the differentiation of cancer and endometrioma.…”
Section: Discussionmentioning
confidence: 90%
“…20 In a study evaluating patients with benign ovarian cysts, endometriomas, and ovarian malignancies, serum IL-10 levels were significantly higher in ovarian cancer patients than the other study groups. 21 In the study by Măluţan et al, 23 the serum IL-10 level was also significantly higher in women diagnosed with endometriosis compared to the control group. Evaluating the serum levels of IL-10, our study found a cut-off value of 12.56 pg/mL in the differentiation of cancer and endometrioma.…”
Section: Discussionmentioning
confidence: 90%
“…Regarding miR-451a, Graham's team has recently published two studies showing increased levels of this miRNA in ovarian endometriomas that correlate with lesion size and with its serum levels (30,31). Provided that PF is mainly composed of blood components (32), and usually up-regulated proteins in serum are proportionally up-regulated in PF (33), our results are in accordance with Graham's, suggesting an important role for miR-451a as a mediator of inflammation in the peritoneal microenvironment. Furthermore, miR-451a has been characterized as the most abundant miRNA in plasma and the main miRNA within erythrocytes (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…[62][63][64][65][66][67] Many cytokines and chemokines including TNF-α, IL-6, IL-8, and CXCL1 are significantly increased in serum, ascites or tumor samples of ovarian cancer patients. [7][8][9][10]30 Biological studies have shown that both ovarian tumor cells and tumor-infiltrating immune cells contribute to elevated levels of TNF-α and other inflammatory mediators in ovarian tumors. 1,2,6 As a primary pro-inflammatory factor, TNF-α acts as an endogenous promoter of a variety of oncogenic processes such as cellular transformation, survival, proliferation, invasion, angiogenesis, and metastasis.…”
Section: F I G U R Ementioning
confidence: 99%
“…1 TNF-α and other inflammatory mediators were detected at elevated levels in the serum and ascites of ovarian cancer patients. [7][8][9][10] It is now well established that, in addition to host immune cells, ovarian tumor cells are a clinically relevant source of these elevated inflammatory cytokines in vivo.…”
Section: Introductionmentioning
confidence: 99%